(untitled) (International Journal of Engineering and Computer Science, 2016)
One of the regular job done by users on the Internet is searching. Information is rapidly growing on the world wide web, hence users are facing difficulties to get effective and efficient search results for their searching terms. Personalization technique is used for providing more effective and relevant search results to user. We study Personalized Web Search engine which refers to the results based on the users’ preferences. But users are not ready to share their personal information while searching process, which has become a main hurdle for large use of Personalized Web Search. Proposed system generalizes profile containing all interest areas related to query from complete user profile while satisfying the privacy requirements defined by users. Here system focuses to maximize the profile utility and minimize privacy risk. Click-log is used for user profile updating and providing page recommendations